Pathological Findings in Quails Infected with Avian Influenza A Virus H7 N1 Subtype - Yilmaz, Fethi; Timurkaan, Necati; Coven, Fethiye (International Journal of Poultry Science, 2004)
The aim of this study was to identify the clinical signs, gross and histopathological findings of the quails experimentally inoculated with Avian Influenza A virus H7 N1 subtype. Two groups of 6-day-old, ninety quails (45 quails were inoculated, 45 quails were kept as control) (Coturnix coturnix japonica) were used. Avian Influenza A virus H7 N1 subtype was inoculated intra nasally into the experimental group of the quails. Decrease in feed and water consumption, calmness, reluctance, and diarrhea were observed as clinical symptoms after the 15 days after of inoculation. Pathologically, mild inflammation with congestion and haemorrhage in the respiratory tract and intestines, degenerative and necrotic changes in the liver and heart, and non suppurative meningoencephalitis were observed. In conclusion, H7N1 of AIV subtype caused a mild form of the disease in quails. The clinical signs and pathological findings were not specific for the diagnosis of the disease. The results of the present study suggest that the cases with the symptoms written above should be taken into consideration of possibility of AI in quails.